Antioxidant and cytotoxic effects of Curcuma mangga and Bosenbergia rotunda ethanolic extracts on Mcf-7 cancer cell lines - Meenakshi Sundram, Tamil Chelvan; Zakaria, Mohd Hazim; Mohd Nasir, Mohd Hamzah (Zibeline International Publishing Sdn. Bhd., 2019)
Curcuma mangga and Bosenbergia rotunda which belongs to Zingiberaceae family are largely distributed in South East Asian countries including Malaysia. These plants have been traditionally used for treatment of various diseases. In this research we focused on determining the antioxidant and cytotoxic activity of C. mangga and B. rotunda ethanolic extracts. Initially, in this study, ethanolic extracts from rhizomes of C. mangga and B. rotunda were obtained through Soxhlet extraction method. 12.6% and 3.5% of crude extract were obtained from C. mangga and B. rotunda respectively. For MTT assay, the IC50 values are 207µg/ml and 31.96 µg/ml for C. mangga and B. rotunda respectively. Meanwhile for the antioxidant activity using DPPH assay, C. mangga showed higher antioxidant activity with IC50 values of 1073µg/ml compared to B. rotunda with IC50 values of 578µg/ml. It can be concluded both extracts showed low inhibitory effect on MCF-7 cancer cells growth and DPPH free radical activity.